Correlation of Skin Pigmentation Changes as a Side Effect of Clofazimine Treatment with Anxiety Level in MDR-TB Patients at Dr. Soebandi Hospital - Sudjarwo, Raisa; Firdaus, Jauhar; Raharjo, Angga (International Journal of Health and Information System, 2025)
Clofazimine, used to treat Multidrug-resistant tuberculosis (MDR-TB), often causes skin pigmentation changes, potentially impacting patients' self-esteem and anxiety. Anxiety represents a common but often underrecognized comorbidity in MDR-TB patients, who are challenged by lengthy treatment regimens, social stigma, and distressing adverse effects. This study aimed to examine this correlation at Dr. Soebandi Hospital. The study utilized an observational analytic method with a cross-sectional design. The population was all MDR-TB patients in Dr. Soebandi hospital, presented from April to May 2024. We recruited 67 patients using a total sampling technique. We analyzed the primary data from the respondents: 1) Respondents' self-rating of skin pigmentation change; 2) Hamilton Anxiety Rating Scale (HARS) score. We also checked the medical records to analyze the respondents' treatment history. The data were analyzed using the chi-square test. Most respondents were male and in a productive age. The chi-square test results show a p-value of 0.822, indicating no significant correlation between skin pigmentation changes and anxiety levels in MDR-TB patients. Clofazimine-induced skin pigmentation changes had no significant correlation with the anxiety levels among MDR-TB Patients at Dr. Soebandi Hospital. Further studies should consider methodological improvements, including prospective design, larger sample size, mixed method, and involvement of dermatology experts in assessing the skin changes induced by clofazimine. Recognizing individual differences in psychological response highlights the need to offer reassurance, counseling, and psychosocial support for MDR-TB patients.